2018
DOI: 10.1038/s41409-018-0117-5
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of non-cryopreserved autologous hematopoietic stem cell transplantation against a cryopreserved strategy

Abstract: Autologous stem cell transplantation (auto-HSCT) is an effective treatment strategy for hematological malignancies. The standard mode of handling hematopoietic progenitors for the autologous procedure (CRYO) consists on its collection and freezing with dimethyl sulfoxide (DMSO) and its subsequent thawing and re-infusion. This process is toxic and expensive. Non-cryopreserved (non-CRYO) is a less expensive mode of auto-HSCT. We designed a comparative study between both strategies performed in two different cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 28 publications
6
25
0
2
Order By: Relevance
“…Another study carried out in two centers in Chile and Spain compared the outcome in patients who underwent ASCT with cryopreserved stem cells (n = 74) and noncryopreserved stem cells (n = 42). A significantly decreased length of hospital stay was observed in the noncryopreserved group at 15 days versus 20 days in the cryopreserved group, accounted by significantly lower febrile neutropenia (40% vs 92%), mucositis (11% vs 64%), and the requirement for total parenteral nutrition (3% vs 16%) 38 . The current study provides further evidence supporting the use of noncryopreserved stem cells for ASCT in patients with HR‐NB.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Another study carried out in two centers in Chile and Spain compared the outcome in patients who underwent ASCT with cryopreserved stem cells (n = 74) and noncryopreserved stem cells (n = 42). A significantly decreased length of hospital stay was observed in the noncryopreserved group at 15 days versus 20 days in the cryopreserved group, accounted by significantly lower febrile neutropenia (40% vs 92%), mucositis (11% vs 64%), and the requirement for total parenteral nutrition (3% vs 16%) 38 . The current study provides further evidence supporting the use of noncryopreserved stem cells for ASCT in patients with HR‐NB.…”
Section: Discussionsupporting
confidence: 52%
“…The cost of stem cell cryopreservation to the patient in India varies from 300 to 700 USD. We did not cryopreserve the stem cells in our cohort, as there was enough literature in support 37‐40 . Besides, it helped financially.…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic stem cells remain viable for several days at 4°C storage [3,4]. Studies with non-cryopreserved HSCs are limited [1,2,[5][6][7][8]. In support of these, we report the outcome of ASCT in MM and lymphoma with mobilized non-cryopreserved peripheral blood stem cell (PBSC) graft in 76 patients in terms of feasibility, safety, and efficacy.…”
mentioning
confidence: 95%
“…Another study has in fact demonstrated that noncryopreserved stem cells are superior to cryopreserved stem cells with faster engraftment, lower incidence of febrile neutropenia and shorter hospital stay after the transplantation procedure [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation